Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil